HACE1 is a potential tumor suppressor in osteosarcoma - El-Naggar, Amal M; Clarkson, Paul W.; Negri, Gian Luca; Turgu, Busra; Zhang, Fan; Anglesio, Michael S.; Sorensen, Poul H. (Cell death & disease, 2019)
Osteosarcoma is a malignant bone sarcoma characterized by extensive genomic disruption and a propensity for metastatic spread. Osteoid production suggests a close relationship with normal osteoblasts, and the latter are the presumptive cell of origin of this disease. The HACE1 gene, localized to human chromosome 6q21, encodes the HACE1 HECT E3 ligase, a tumor suppressor in diverse tumors that acts in part by targeting the activated form of RAC1 GTPase for proteasomal degradation. Disruption or loss of 6q21 is relatively common in osteosarcomas, and Hace1−/−/Tp53 +/ − mice frequently develop osteosarcomas, in contrast to Tp53 +/− mice, which do not. This suggests an unexplored link between HACE1 loss and osteosarcoma. Here we compared HACE1 expression in normal osteoblasts and osteosarcoma cell lines in vitro by western blotting and quantitative RT-PCR, and in human osteosarcoma specimens by immunohistochemistry. Both HACE1 transcript and protein levels were reduced in osteosarcoma compared to osteoblasts in vitro. Reduced HACE1 expression in osteosarcoma tumors was observed in 76% of cases and associated with high-grade lesions. Further, clonally derived pairs of high and low metastatic osteosarcoma cell lines showed significant downregulation in the high compared to corresponding low metastatic cells. Ectopic expression of HACE1 markedly inhibited anchorage-independent growth and cell motility of HACE1 osteosarcoma cell lines, and was associated with reduced RAC1 activation and decreased reactive oxygen species (ROS). Finally, HACE1 overexpression blocked osteosarcoma xenograft growth and dramatically reduced pulmonary metastases. These findings point to a potential tumor suppressor function for HACE1 in osteosarcoma.